The practice-changing QUARTZ trial: is there any role for whole brain radiotherapy in patients with non-small cell lung cancer and brain metastases? - Sais, Elia; Menéndez, Javier A.; Bosch-Barrera, Joaquim (Translational Cancer Research; Vol 6, Supplement 1 (February 28, 2017): Translational Cancer Research, 2017)
Brain metastases (BM) remain a substantial source of morbidity and mortality in patients with lung cancer. Current clinical management of BM involves a combination of supportive care, brain radiotherapy and systemic treatment against the tumor. Whole brain radiotherapy (WBRT) has been a cornerstone in the treatment of BM for decades. Recently, the QUARTZ trial, a phase 3, non-inferiority, randomized clinical trial addressing the efficacy of best supportive care (BSC) alone or with WBRT in patients with NSCLC reported no differences in survival or quality of life between the two groups. In this perspective article, we will discuss the QUARTZ trial results and their implications for clinical practice. We will also discuss potential biomarkers that could be used to identify patients with radioresistance. This molecular approach might help, in addition to clinical variables, to define the patients that will obtain less benefit from WBRT and/or to design new targeted therapies to reverse radioresistance and improve the results of radiotherapy treatment when indicated.